Buddhism Re-Evaluated by Prominent 20th Century Hindus - Klaus K Klostermaier (Journal of Dharma, 1995)
By the 15th century, when Buddhism had all but disappeared from its homeland India, Hindu-Buddhist polemics. which were continued in scholarly circles, had degenerated into mere stereotype. Buddhism was equated with atheism, with nihilism and with contempt for the traditional ethos. Most of the authors who repeated and enlarged upon anti-Buddhist arguments as found in the Puranas and in the writings of the great Vedantacaryas never had an opportunity to encounter a Buddhist, let alone debate points of philosophy and religion with a Buddhtst scholar,l Sheer inertia made Hindu scholastic texts perpetuate a debate which had long before become meaningless. Mere animosity made Hindu scholars use the term "Bauddha" as an invective to silence opinions other than their own, when they ran out of rational arguments to make their point.